EFFECT OF DIFFERENT IRRIGATION FREQUENCIES AND METHODS ON PERFORMANCE OF POTATO IN NORTH-EASTERN GHATS OF ODISHA - Mondal, Triptesh; Vytla, Sravya; Rajesh Shriram Kalasare; Tanmoy Shankar; Dinkar J. Gaikwad (Journal of the Indian Potato Association : official journal of the Indian Potato Association, Central Potato Research Institute, 2025)
An experiment was conducted at CUTM, Odisha to evaluate the influence of different irrigation frequenciesand methods on performance of potato. The experiment was designed in strip plot design with 4 irrigation frequenciesand 3 irrigation methods together, replicated thrice. The significantly higher LAI at 60 DAP, haulm dry weight at 60 and86 DAP, chlorophyll total at 60 and 75 DAP were recorded with 20 mm ETc than all other irrigation frequencies. In caseof irrigation methods, every furrow irrigation (EFI) showed significantly higher LAI at 60 DAP, dry weight of tubers at86 DAP, arithmetic and geometric mean diameter of grade A tubers, chlorophyll total content at 60 and 75 DAP than allothers. The maximum tuber yield was recorded with 20 mm ETc which was statistically at par with 30 mm ETc. But higheststarch content was recorded under 30 mm ETc and it was significantly decreased at 20 mm ETc due to plenty of soil moistureunder this treatment. Starch content was also decreased significantly under EFI than AFI due to the same fact. The tuberyield obtained under EFI was statistically at par with alternate furrow irrigation (AFI). According to the linear regression,proportionate tuber yield increase will be higher with decrease in the irrigation water use efficiency. The treatmentcombination, 20 mm ETc-EFI showed highest gross return, net return and B:C which could be recommended for the potatogrowers in north-eastern ghats of Odisha. This was closely followed by the treatment combination, 30 mm ETc-EFI or 20mm ETc-AFI and could also be adopted as a remunerative technique in the areas having water crisis.